Realizing Job Satisfaction and Performance through Organizational Culture and Job Involvement - Feri Djoko Riyanto; Tetra Hidayati; Saida Zainurossalmia (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2020)
Human resource management is an important aspect of an organization. The quality of human resources must be developed every time for the organization to achieve the expected goals. This study aims to determine and analyze the influence of organizational culture and involvement on performance mediated by job satisfaction at the Regional Office of Direktorat Jendral Kekayaan Negara Kalimantan Timur dan Utara. This research uses quantitative approach with a survey method on 41 respondents. Testing uses descriptive and path analysis. The results showed that job satisfaction does’t automatically increase productivity. Organizational culture and involvement have an influence on job satisfaction, besides that it can be concluded that employee dissatisfaction tends to reduce employee productivity.